2015
DOI: 10.1371/journal.pone.0133982
|View full text |Cite
|
Sign up to set email alerts
|

The Gonococcal Transcriptome during Infection of the Lower Genital Tract in Women

Abstract: Gonorrhea is a highly prevalent disease resulting in significant morbidity worldwide, with an estimated 106 cases reported annually. Neisseria gonorrhoeae, the causative agent of gonorrhea, colonizes and infects the human genital tract and often evades host immune mechanisms until successful antibiotic treatment is used. The alarming increase in antibiotic-resistant strains of N. gonorrhoeae, the often asymptomatic nature of this disease in women and the lack of a vaccine directed at crucial virulence determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…The importance of these proteins is shown by the avirulent nature of a tbp-deficient strain of N. gonorrhoeae in experimental infection of the male genital tract in humans (24). In addition, we have reported that fur, tbpB, and fbp are expressed during natural gonococcal infection, supporting a role for Fur-mediated control of gene expression during the pathogenic process (2,3,25).…”
mentioning
confidence: 69%
“…The importance of these proteins is shown by the avirulent nature of a tbp-deficient strain of N. gonorrhoeae in experimental infection of the male genital tract in humans (24). In addition, we have reported that fur, tbpB, and fbp are expressed during natural gonococcal infection, supporting a role for Fur-mediated control of gene expression during the pathogenic process (2,3,25).…”
mentioning
confidence: 69%
“…None of these comparisons achieved statistical significance by chisquare analysis. The lack of overlap may be because these regulons were determined by comparing differential gene expression in strains where the regulator was either present or induced to that of a strain where the regulator was either absent (54)(55)(56)(57)(58)(59)(60). Several of these studies reported the upregulation of genes involved in the transport of transition metals, peptides, and amino acids during human infection.…”
Section: Fig 3 Qrt-pcr Validation Of the Rna-seq Data The Fold Changmentioning
confidence: 99%
“…Other species known to respond to surface adherence by triggering transcriptional changes include Neisseria meningitidis , Caulobacter crescentus , and Trichomonas vaginalis . Interestingly, not all of these changes are directly implicated in bacterial pathogenicity — often they affect global functions underpinning bacterial physiology, including DNA and RNA processing, genome stability, and bacterial metabolism [2730]. In conclusion, if a bacterium adheres to a surface, no matter if this is a short-lived or prolonged interaction, this can be termed colonization.…”
Section: Introductionmentioning
confidence: 99%